Iatrogenic Bile Duct Injuries Following Laparoscopic Cholecystectomy: Myth or Reality? A Recent Literature Review from 2006 to 2011 - Conzo, Giovanni; Napolitano, Salvatore; Candela, Giancarlo; Palazzo, Antonietta; Stanzione, Francesco; Mauriello, Claudio; Santini, Luigi (IntechOpen, 2012)
None